2022
DOI: 10.2147/ijn.s387590
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Graphene Oxide Contributes to Alteration of Key Stress-Related and Membrane Bound Proteins

Abstract: Antibacterial activity of graphene oxide (GO) has been extensively studied, wherein penetration of the bacterial cell membrane and oxidative stress are considered to play a major role in the bactericidal activity of GO. However, the specific mechanism responsible for the antibacterial activity of GO remains largely unknown. Hence, the goal of this study was to explore the mode of action of GO, via an in-depth proteomic analysis of the targeted bacteria. Methods: Staphylococcus aureus was grown in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The physical interaction of pGO with bacterial strains is most often the result of physical damage to the outer membranes of bacteria by the sharp edges of graphene. Chemically, graphene paper, like other graphene materials, can lead to oxidative stress generated by charge transfer and the formation of reactive oxygen species (ROSs) [ 38 ]. In our study, the antibacterial activity of pGO resulted from a combination of the mechanisms of action of selected antibiotics and the physicochemical properties of graphene itself, limiting bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…The physical interaction of pGO with bacterial strains is most often the result of physical damage to the outer membranes of bacteria by the sharp edges of graphene. Chemically, graphene paper, like other graphene materials, can lead to oxidative stress generated by charge transfer and the formation of reactive oxygen species (ROSs) [ 38 ]. In our study, the antibacterial activity of pGO resulted from a combination of the mechanisms of action of selected antibiotics and the physicochemical properties of graphene itself, limiting bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene oxide (GO) has been reported for its antimicrobial activity against a range of Gram-positive and Gram-negative bacterial strains ( Liu et al., 2011 ; Chen et al., 2014 ; Romero et al., 2020 ). The antimicrobial activity of GO is mainly due to cell wrapping/trapping, insertion, damage of cell membrane, and generation of oxidative stress ( Zou et al., 2017 ; Pulingam et al., 2019 ; Chen et al., 2021 ; Ravikumar et al., 2022 ). Our recent study demonstrated the correlation of time-dependent bacteriostatic and bactericidal effects of GO with changes in the cell membrane and expression of stress-associated proteins ( Ravikumar et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of GO is mainly due to cell wrapping/trapping, insertion, damage of cell membrane, and generation of oxidative stress ( Zou et al., 2017 ; Pulingam et al., 2019 ; Chen et al., 2021 ; Ravikumar et al., 2022 ). Our recent study demonstrated the correlation of time-dependent bacteriostatic and bactericidal effects of GO with changes in the cell membrane and expression of stress-associated proteins ( Ravikumar et al., 2022 ). However, the antimicrobial intensity of pristine GO alone is not sufficient to kill bacterial cells on a large scale and inside bacterial communities such as biofilms ( Pandit et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%